2020
DOI: 10.1111/ajt.15607
|View full text |Cite
|
Sign up to set email alerts
|

Transplant candidates’ perceptions of informed consent for accepting deceased donor organs subjected to intervention research and for participating in posttransplant research

Abstract: Deceased donor organ intervention research holds promise for increasing the quantity and quality of organs for transplantation by minimizing organ injury and optimizing function. Such research will not progress until ethical, regulatory, and legal issues are resolved regarding whether and how to obtain informed consent from transplant candidates offered intervention organs given time constraints intrinsic to distribution. This multi‐center, mixed‐methods study involved semi‐structured interviews using open‐ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 18 publications
3
21
0
Order By: Relevance
“…The survey also included questions on participants’ demographics, health literacy (or an individual's ability to "obtain, process, and understand basic health information and services needed to make appropriate health decisions" 22 using a validated measure), 23,24 and clinical characteristics. The survey assessed trust in physicians and health‐related quality of life because prior research identified them as important factors in hypothetical decision making for intervention organs 20 . The validated SF‐12v2 25 assessed generic health‐related quality of life using 12 items, with subscores ranging from 0‐100; higher scores reflect greater quality of life 26 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey also included questions on participants’ demographics, health literacy (or an individual's ability to "obtain, process, and understand basic health information and services needed to make appropriate health decisions" 22 using a validated measure), 23,24 and clinical characteristics. The survey assessed trust in physicians and health‐related quality of life because prior research identified them as important factors in hypothetical decision making for intervention organs 20 . The validated SF‐12v2 25 assessed generic health‐related quality of life using 12 items, with subscores ranging from 0‐100; higher scores reflect greater quality of life 26 .…”
Section: Methodsmentioning
confidence: 99%
“…Only a small number of studies about decision making in transplantation have focused on patient preferences for accepting organs 16,17 or for organ allocation 18,19 . Our prior qualitative research identified organ quality, trust in their physician, and their health status as factors affecting candidates’ willingness to accept intervention organs 20 …”
Section: Introductionmentioning
confidence: 99%
“…The decision to donate organs generally requires positive perception toward donation. Studies show that DPs are shaped by trust, 17,18 attitude, 19,20 and knowledge 21,22 about organ donation. 23,24 One of the important barriers across various groups that has discouraged donation is distrust in the medical system.…”
Section: Factors Influencing Wtdmentioning
confidence: 99%
“…Gordon and team for providing some extremely helpful information regarding transplant candidates' perceptions of informed consent for organs procured from donors undergoing intervention trials (DITs). 1 Their finding that most candidates wish to be informed about the nature of a donor intervention trial is not surprising. Moreover, it is extremely beneficial to know their subjects were supportive of participating in such trials if they are given adequate information to make an informed choice.…”
Section: Clarifying Donor Intervention Trialsmentioning
confidence: 99%